Analysis of Th Cell-related Cytokine Production in Behçet Disease Patients with Uveitis Before and After Infliximab Treatment. (2nd January 2017) - Takeuchi, Masaru; Karasawa, Yoko; Harimoto, Kohzou; Tanaka, Atsushi; Shibata, Masaki; Sato, Tomohito; Caspi, Rachel R.; Ito, Masataka
ABSTRACT: Purpose : To examine antigen-stimulated cytokine production by Behçet disease patients (BD) before and after infliximab infusion. Methods : PBMCs were obtained before and after infliximab infusion in BD patients with or without recurrent uveitis during at least 1 year of infliximab therapy, and from healthy subjects. PBMCs were cultured with IRBP, and Th-related cytokines in cultures were measured. Results : Levels of IL-4, IL-6, IL-10 IL-17A, IL-17F, IL-31, IFN-γ, and TNFα were higher in BD before infliximab infusion than in healthy subjects, and these levels were the highest in BD with recurrent uveitis. After infliximab infusion, these cytokine levels were reduced to a greater extent in BD without recurrent uveitis than in BD with recurrence. Conclusions : Th-related cytokines produced by IRBP-stimulated PBMCs were elevated in BD, and infliximab infusion suppressed these cytokines to a greater extent in BD without recurrent uveitis than in those with recurrence.